Ta’lÃ®m al-MufradÃ¢t al-’Arabiyyah ’alÃ¢ TharÃ®qati al-IstidzkÃ¢r Mnemonic lil al-KalimÃ¢t al-MiftÃ¢hiyyah - Nasir, Amin; Basit, Mohammad Abdul (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2021)
This study discusses the mnemonic method of remembering key words for middle school children. The background of this study is that many students at school find it difficult and less responsive to vocabulary mastery in students. Use this mnemonic method for keywords we apply in the eighth semester in middle school. To determine the effect of using the mnemonic method effectively for success, we apply the eighth semester students in high school. This research is a quasi-experimental research. The use of the mnemonic method for keywords in the eighth semester of middle school. Based on the post-test scores, learning uses the mnemonic method for keywords. Its value is 85.59, as an average. Mastering Arabic vocabulary among students before using the mnemonic method for data-based key words. The pre-test mean score of students’ Arabic vocabulary mastery in the experimental semester was 66.07 and the mean score in the control class was 62.18. As well as mastering the students’ Arabic vocabulary after treatment.Ø§Ù„Ø¨Ø§Ø±ÙŠØŒ Ù…Ø§Ù‡Ø± Ø´Ø¹Ø¨Ø§Ù† Ø¹Ø¨Ø¯. ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ù„ØºÙˆÙŠØ©. Ø¹Ù…Ø§Ù†: Ø¯Ø§Ø± Ø§Ù„Ù…Ø³ÙŠØ±Ø©ØŒ Ù¢Û°Ù¡Ù¡. Ø§Ù„Ø´ÙŠØ®ØŒ Ø§Ù„ØØ§ÙØ¸ Ø¹Ø¨Ø¯ Ø§Ù„Ø±ØÙŠÙ…. ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØºÙŠØ± Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§. Ø¥Ø±Ø¨Ø¯: Ø¹Ø§Ù„Ù… Ø§Ù„ÙƒØªØ¨ Ø§Ù„ØØ¯ÙŠØ«ØŒ Ù¢Û°Ù¡Ù£. Ø§Ù„Ø¶Ø§Ù…Ù†ØŒ Ù…Ù†Ø°Ø±. Ø£Ø³Ø§Ø³ÙŠØ§Øª Ø§Ù„Ø¨ØØ« Ø§Ù„Ø¹Ù„Ù…ÙŠ. Ø¹Ù…Ø§Ù†: Ø¯Ø§Ø± Ø§Ù„Ù…Ø³ÙŠØ±Ø©ØŒ Ù¢Û°Û°Ù§. Ø§Ù„Ù†Ø§Ù‚Ø©ØŒÂ Ù…ØÙ…ÙˆØ¯ ÙƒØ§Ù…Ù„ Ùˆ Ø±Ø´Ø¯ÙŠ Ø£ØÙ…Ø¯ Ø·Ø¹ÙŠÙ…Ø©.Â Ø·Ø±Ø§Ø¦Ù‚ Ø§Ù„ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØºÙŠØ± Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§. Ø§Ù„Ø±Ø¨Ø§Ø·: Ø¥ÙŠØ³ÙŠØ³ÙƒÙˆØŒ Ù¢Û°Û°Ù£. Ø§Ù„Ù‡ÙŠØ¬Ø§Ø¡ØŒ ÙØ¤Ø§Ø¯ ØØ³Ù† ØØ³ÙŠÙ† Ø£Ø¨Ùˆ. Ø£Ø³Ø§Ù„ÙŠØ¨ ÙˆØ·Ø±Ù‚ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ¥Ø¹Ø¯Ø§Ø¯ Ø¯Ø±ÙˆØ³Ù‡Ø§ Ø§Ù„ÙŠÙˆÙ…ÙŠØ©. Ø§Ù„Ø£Ø±Ø¯Ù†: Ø¯Ø§Ø± Ø§Ù„Ù…Ù†Ø§Ø²Ø¹ Ù„Ù„Ù†Ø´Ø± ÙˆØ§Ù„ØªÙˆØ²ÙŠØ¹ØŒ Ù¢Û°Û°Ù§. Ø¨Ø±Ø§ÙˆÙ†, Ø¯ÙˆØ¬Ù„Ø§Ø³. Ù…Ø¨Ø§Ø¯Ø¦ ØªØ¹Ù„Ù… ÙˆØ§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ©.Terjemahan olehÂ Ø¥Ø¨Ø±Ø§Ù‡ÙŠÙ… Ø¨Ù† ØÙ…Ø¯ Ø§Ù„Ù‚Ø¹ÙŠØ¯ Ùˆ Ø¹ÙŠØ¯ Ø¨Ù† Ø¹Ø¨Ø¯ Ø§Ù„Ù„Ù‡ Ø§Ù„Ø´Ù…Ø±ÙŠ. Ø§Ù„Ø±ÙŠØ§Ø¶: Ù…ÙƒØªØ¨ Ø§Ù„ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù„Ø¯ÙˆÙ„ Ø§Ù„Ø®Ù„ÙŠØ¬ØŒ Ù¡Ù©Ù©Ù¤. Ø·Ø¹ÙŠÙ…Ø©ØŒ Ø±Ø´Ø¯ÙŠ Ø£ØÙ…Ø¯ØŒ Ùˆ Ù…ØÙ…ÙˆØ¯ ÙƒØ§Ù…Ù„ Ø§Ù„Ù†Ø§Ù‚Ø©. ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø¥ØªØµØ§Ù„ÙŠØ§ Ø¨ÙŠÙ† Ø§Ù„Ø¯Ù†Ø§Ø¯Ø¬ ÙˆØ§Ù„Ø¥Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ§Øª. Ø§Ù„Ø±Ø¨Ø§Ø·: Ø¥ÙŠØ³ÙŠØ³ÙƒÙˆØŒ Ù¢Û°Û°Ù¦. Ø·Ø¹ÙŠÙ…Ø©ØŒ Ø±Ø´Ø¯ÙŠ Ø£ØÙ…Ø¯.Â ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØºÙŠØ± Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§ Ù…Ù†Ø§Ù‡Ø¬Ù‡ ÙˆØ£Ø³Ø§Ù„ÙŠØ¨Ù‡. Ø§Ù„Ø±Ø¨Ø§Ø·: Ø¥ÙŠØ³ÙŠØ³ÙƒÙˆØŒ Ù¡Ù©Ù¨Ù©. Ø·Ø¹ÙŠÙ…Ø©ØŒ Ø±Ø´Ø¯ÙŠ Ø£ØÙ…Ø¯. Ù…Ù†Ø§Ù‡Ø¬ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø£Ø³Ø§Ø³ÙŠ. Ø§Ù„Ù‚Ø§Ù‡Ø±Ø©: Ø¯Ø§Ø± Ø§Ù„ÙÙƒØ± Ø§Ù„Ø¹Ø±Ø¨ÙŠØŒ Ù¡Ù©Ù©Ù¨. Ù‡Ø§Ù†Ø¯Ù„ÙŠØŒÂ Ø¨ÙŠÙ„.Â ØªØ¹Ù„Ù… Ù„ØºØ© Ø¬Ø¯ÙŠØ¯Ø© Ø¨Ø³Ø±Ø¹Ø© ÙˆØ³Ù‡ÙˆÙ„Ø©.Terjemahan oleh.Â ÙØ§ÙŠÙ‚Ø© Ø¬Ø±Ø¬Ø³ ØÙ†Ø§. Ø§Ù„Ù‚Ø§Ù‡Ø±Ø©: Ù…Ø¤Ø³Ø³Ø© Ù‡Ù†Ø¯Ø§ÙˆÙŠ Ù„Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„Ø«Ù‚Ø§ÙØ©ØŒ Ù¢Û°Ù¡Ù§. Al-Bantani, Syekh Nawawi. Kitab Nashaihul â€˜Ibad (Kumpulan Nasihat Pilihan Bagi Para Hamba). Terjemahan oleh Fuad Saifudin Nur, diedit oleh Yusni Amru Ghozali dan Agus Khudhori. Jakarta: Wali Pustaka, 2017. Al-Qur’an dan Terjemahnya, Jakarta: Departemen Agama R I, Yayasan Penyelenggara Penterjemah Al-Qur’an, 1989. Amalia, Fitri Ayu. â€œPenerapan Metode Index Card Match Terhadap Penguasaan Kosa Kata Bahasa Arab Peserta Didik Dikelas III A Min 2 Bandar Lampung.â€ Skripsi, UIN Raden Intan Lampung, 2017 - 22 Januari, 2019 - http://repository.radenintan.ac.id/3696/1/SKRIPSI%20LENGKAP.pdf. Anshorulloh, Romi. â€œEfektivitas Metode Mnemonik Dalam Meningkatkan Daya Ingat Siswa Pada Mata Pelajaran Sejarah Di MTs Persiapan Negeri Kota Batu.â€ Skripsi, Universitas Islam Negeri Malang, 2008 - 22 Januari, 2019 -Â http://etheses.uin-malang.ac.id/4320/1/02410022.pdf. Arifin, Zainal. Penelitian Pendidikan, dieditoleh Adriyani Kamsyah. Bandung: PT Remaja Rosdakarya, 2014. Arikunto, Suharsimi. Prosedur Penelitian, Suatu Pendekatan Praktik. Jakarta: PT Rineka Cipta, 2010. Ary, Donald, Luchy Cheser Jacobs, and Asghar Razavieh. Pengantar Penelitian Dalam Pendidikan. Terjemahan oleh Arief Furchan. Yogyakarta: Pustaka pelajar, 2005. Asmarani, Kartika. â€œEfektifitas Metode Mnemonik Dalam Meningkatkan Daya Ingat Siswa Kelas IX SMP Negeri 2 Satu Atap Sluke Pada Mata Pelajaran Sejarah Tahun Pelajaran 2012/2013.â€ Skripsi, Universitas Negeri Semarang, 2013 - 22 Januari, 2019 - https://lib.unnes.ac.id/18880/1/3101407003.pdf. Darmadi, Hamid. Metode Penelitian Pendidikan Dan Sosial: Teori Konsep Dasar Dan Implementasi. Bandung: Alfabeta, 2014. Davidoff, Linda L. Psikologi Suatu Pengantar. Terjemahan oleh Mari Juniati. Jakarta: Erlangga, 1988. Dermawanti, Ayu. â€œPengaruh Penggunaan Metode Mnemonik Terhadap Peningkatan Kemampuan Mengingat Pada Mata Pelajaran Ilmu Pengetahuan Sosial.â€ Skripsi, Universitas Pendidikan Indonesia, 2016 - 22 Januari, 2019 - http://repository.upi.edu/27250/2/S_KTP_1201884_Abstract.pdf. Djamarah, Syaiful Bahri, dan Aswan Zain. Strategi Belajar Mengajar. Jakarta: PT. Rineka Cipta, 2010. Effendy, Ahmad Fuad. Metodologi Pengajaran Bahasa Arab. Malang: Misykat, 2012. Fahrurrozi, Aziz, dan Erta Mahyudin. Pembelajaran Bahasa Asing Tradisional Dan Kontemporer. Jakarta, Raja Grafindo Persada, 2016. Fahrurrozi, Aziz. â€œPembelajaran Bahasa Arab: Problematika Dan Solusinya.â€ Arabiyat: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban 1, no. 2 (2014) - 25 Januari, 2019 - http://www.academia.edu/11682295/PEMBELAJARAN_BAHASA_ARAB_PROBLEMATIKA_DAN_SOLUSINYA. Fasih, Parima, Sirod Izadpanah, dan Ali Shahnavaz. â€œThe Effects of Mnemonic Vocabulary Instruction on Content Vocabulary Learning of Students,â€ Journal of Language & Education 4, no. 1 (2018) - 22 Januari, 2019 - https://jle.hse.ru/article/view/7127/8513. Hasibuan, Annalisa Sonaria. â€œPenggunaan Metode Mnemonik Dengan Teknik Linkword Dalam Penguasaan Kosakata Dasar Bahasa Jepang.â€ Tesis, Universitas Pendidikan Indonesia, 2016 - 22 Januari, 2019 - http://repository.upi.edu/22788/2/T_B.JPN_1302201_Abstract.pdf. Hermawan, Acep, dan Chaedar Alwasilah. Metodologi Pembelajaran Bahasa Arab. Bandung: PT Remaja Rosdakarya, 2011. Huda, Miftahul. Model-Model Pengajaran Dan Pembelajaran Isu-Isu Metodis Dan Paradigmatis. Yogyakarta: Pustaka Pelajar, 2017. Islamuddin, Haryu. Psikologi Pendidikan. Jember: STAIN Jember Press, 2014. Jakni. Metode Penelitian Eksperimen Bidang Pendidikan. Bandung: Alfabeta, 2016. KayaaltÄ±, Mahmut. â€œMnemonic Technique-An Effective Vocabulary Teaching Method to Plurilingual Students.â€ Modern Journal Of Language Teaching Methods 8, no. 5 (2018) - 22 Januari, 2019 - https://mjltm.org/article-1-219-en.pdf. Khodijah, Nyayu. Psikologi Pendidikan. Jakarta: PT. Raja Grafindo Persada, 2014. Khuluqo, Ihsana El. Belajar Dan Pembelajaran Konsep Dasar, Metode, dan Aplikasi Nilai-Nilai Spiritualitas dalam Proses Pembelajaran. Yogyakarta: Pustaka Pelajar, 2017. Mahmud. Metode Penelitian Pendidikan. Bandung: CV Pustaka Setia. Bandung, 2011. Masrukhin. Statistik Inferensial Aplikasi Program SPSS. Kudus: Media Ilmu Press, 2008. Mulyatiningsih, Endang. Metode Penelitian Terapan Bidang Pendidikan, diedit oleh Apri Nuryanto. Bandung: Alfabeta, 2013. Mustofa, Bisri, dan M Abdul Hamid. Metode Dan Strategi Pembelajaran Bahasa Arab, diedit oleh Imam Muslimin. Malang: UIN-Maliki Press, 2012. Mustofa, Syaiful. Strategi Pembelajaran Bahasa Arab Inovatif. Malang: UIN-Maliki Press, 2011. Nasir, M Ridlwan. Mencari Tipologi Format Pendidikan Ideal: Pondok Pesantren Di Tengah Arus Perubahan. diedit oleh M Adib Abdushomad. Yogyakarta: Pustaka Pelajar, 2005. Nuha, Ulin. Metodologi Super Efektif Pembelajaran Bahasa Arab, diedit oleh Dirusdi Toanto. Yogyakarta: Diva Press, 2012. Nuha, Ulin. Ragam Metodologi & Media Pembelajaran Bahasa Arab. Yogyakarta: Diva Press, 2016. Priyatno, Dwi. SPSS 22 Pengolahan Data Terpraktis. Yogyakarta: Andi Offset, 2014. Rahmatia, Baiq Winda. â€œPenerapan Metode Mnemonic Berbantuan Media Gambar Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas IV SDN 42 Mataram Tahun 2017/2018.â€ Skripsi, Universitas Mataram, 2018 - 22 Januari, 2019 - http://eprints.unram.ac.id/1654/1/SKRIPSI%20BAIQ%20WINDA%20RAHMATIA.pdf. Riadi, Edi. Statistika Penelitian (Analisis Manual Dan IBM SPSS). Yogyakarta: Andi Offset, 2016. Rohmah, Noer. Psikologi Pendidikan, diedit oleh Sutomo. Yogyakarta: Kalimedia, 2015. Saebani, Beni Ahmad, dan Hendra Akhdiyat. Ilmu Pendidikan Islam, diedit oleh Maman Abd Jalil. Bandung: CV Pustaka Setia, 2012. Siregar, Syofian. Metode Penelitian Kuantitatif Dilengkapi Dengan Perbandingan Perhitungan Manual & SPSS. Jakarta: Kencana, 2017. Subana, Moersetyo Rahadi, dan Sudrajat. Statistik Pendidikan. Bandung: Pustaka Setia, 2000. Subur. Pembelajaran Nilai Moral; Berbasis Kisah. Yogyakarta: Kalimedia, 2015. Sudirman, Nur Andini, dan Andi Ahmad Ridha. â€œEfektifkah Keyword Mnemonic Dalam Mempelajari Kosakata?â€ Jurnal Ilmiah Psikologi Terapan 5, no. 2 (2017) - 23 Juli, 2019 - http://ejournal.umm.ac.id/index.php/jipt/article/viewFile/4639/pdf. Sugiyono. Metode Penelitian Pendidikanâ€¯: Pendekatan Kuantitatif, Pendekatan Kualitatif, Dan R&D. Bandung: Alfabeta, 2017. Sugiyono. Statistika Untuk Penelitian. Bandung: Alfabeta, 2014. Suharsono. Melejitkan IQ, EQ, SQ. Jakarta: Ummah Publishing, 2009. Syafril, dan Zelhendri Zen. Dasar-Dasar Ilmu Pendidikan. Depok: Kencana, 2017. Syarbini, Amirullah. Pendidikan Karakter Berbasis Keluarga Studi Tentang Model Pendidikan Karakter Dalam Perspektif Islam, diedit oleh Aziz Safa. Yogyakarta: Ar-ruzz Media, 2017. Tafsir, Ahmad. Ilmu Pendidikan Islam. Bandung: PT Remaja Rosdakarya, 2013. Whitescarver, Erin L. â€œEffect of Mnemonics on the Vocabulary Acquisition and Retention of High School Students with Learning Disabilities.â€ Tesis, Rowan University, 2018 - 22 Januari, 2019 - https://pdfs.semanticscholar.org/58a4/13918c0d1ebff5f932ad4e9971ddf5f9a90b.pdf. Woolfolk, Anita E, dan Lorraine McCune-Nicolich. Mengembangkan Kepribadian Dan Kecerdasan. Terjemahan oleh M Khairul Anam. Jakarta: Inisiasi Press, 2004.